Genomic Alterations of NTRK, POLE, ERBB2, and Microsatellite Instability Status in Chinese Patients with Colorectal Cancer. (10th August 2020) - Guo, Yun; Guo, Xian‐ling; Wang, Shuang; Chen, Xinyu; Shi, Jiaochun; Wang, Jian; Wang, Kai; Klempner, Samuel J.; Wang, Weifeng; Xiao, Min
Abstract: Background: The increasing molecular characterization of colorectal cancers (CRCs) has spurred the need to look beyond RAS, BRAF, and microsatellite instability (MSI). Genomic alterations, including ERBB2 amplifications and mutations, POLE mutations, MSI, and NTRK1 – 3 fusions, have emerged as targets for matched therapies. We sought to study a clinically annotated Chinese cohort of CRC subjected to genomic profiling to explore relative target frequencies. Methods: Tumor and matched whole blood were collected from 609 Chinese patients with CRC. Extracted DNA was analyzed for all classes of genomic alterations across 450 cancer‐related genes, including single‐nucleotide variations (SNVs), short and long insertions and deletions (indels), copy number variations, and gene rearrangements. Next‐generation sequencing–based computational algorithms also determined tumor mutational burden and MSI status. Results: Alterations in TP53 (76%), APC (72%), and KRAS (46%) were common in Chinese patients with CRC. For the first time, the prevalence of NTRK gene fusion was observed to be around 7% in the MSI‐high CRC cohort. Across the cohort, MSI was found in 9%, ERBB2 amplification in 3%, and POLE pathogenic mutation in 1.5% of patients. Such results mostly parallel frequencies observed in Western patients. However, POLE existed at a higher frequency and was associated with large tumor T‐cell infiltration. Conclusion: Comparing to the Western counterparts, POLE mutations were increased in our cohort. The prevalence of NTRK gene fusion was around 7% in the MSI‐high CRC cohort. Increased adoption of molecular profiling in Asian patients is essential for the improvement of therapeutic outcomes. Implications for Practice: The increasing use of genomic profiling assays in colorectal cancer (CRC) has allowed for the identification of a higher number of patient subsets benefiting from matched therapies. With an increase in the number of therapies, assays simultaneously evaluating all candidate biomarkers are critical. The results of this study provide an early support for the feasibility and utility of genomic profiling in Chinese patients with CRC. Abstract : The emergence of precision medicine has identified genomic variants, such as NTRK gene fusion, microsatellite instability (MSI), HER2 amplification, and POLE pathogenic mutation, as potential agonistic biomarkers for immune or targeted therapies. This article examines NTRK, HER2, and POLE in a cohort of Chinese patients with colorectal cancer.